Inhibition of Mammary Gland Cancer Development by Propolis and Mangostin in Female Mice Balb/C - Tan, Marselina Irasonia; Hayati, Irham (Journal of Mathematical and Fundamental Sciences, 2017)
The development of breast cancer involves many processes, including angiogenesis and metastasis. Some factors play a major role in angiogenesis, such as HIF-1Î±, and in metastasis, such as FAK and Wnt2. The aim of this study was to observe the effect of propolis and mangostin on the development of mammary gland cancer and on the expression of Wnt2 and FAK in Balb/C mice. Mammary gland tumors were induced in Balb/C mice by DMBA. The mice were divided into 5 treatment groups: negative control (K"‘); positive control treated with doxorubicin (14.04 mg/kg bw) (Dx); mice treated with propolis (0.32 mg/kg bw) (P) or mangostin (0.128 mg/kg bw) (M); and mice treated with a combination of propolis (0.32 mg/kg bw) and mangostin (0.128 mg/kg bw) (MP). Both mangostin and propolis did not affect the body weight of the mice. Treatment with propolis or treatment with propolis combined with mangostin was able to reduce tumor development activity in Balb/C mice. Moreover, the combination of mangostin and propolis was able to lower Wnt2, FAK and HIF-1Î± expression. It can be concluded that the combination of propolis and mangostin has potential to inhibit cancer development through downregulation of Wnt2, FAK, and HIF1Î± expression.